2021
DOI: 10.1257/jep.35.3.3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the COVID-19 Recession on the US Labor Market: Occupation, Family, and Gender

Abstract: The economic crisis associated with the emergence of the novel corona virus is unlike standard recessions. Demand for workers in high contact and inflexible service occupations has declined while parental supply of labor has been reduced by lack of access to reliable child care and in-person schooling options. This has led to a substantial and persistent drop in employment and labor force participation for women, who are typically less affected by recessions than men. We examine real-time data on employment, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
141
2
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(153 citation statements)
references
References 26 publications
7
141
2
3
Order By: Relevance
“…Unlike previous recessions, the COVID-19 pandemic has been uniquely devastating to women (Albanesi and Kim, 2021 , Alon et al, 2020a , b , Croda and Grossbard, 2021 , Pitts, 2021 ). Part of the disproportionate burden on women is attributable to the impact of the pandemic on the service sector, which typically employs more women than men (Alon et al, 2020b ).…”
Section: Related Literaturementioning
confidence: 99%
“…Unlike previous recessions, the COVID-19 pandemic has been uniquely devastating to women (Albanesi and Kim, 2021 , Alon et al, 2020a , b , Croda and Grossbard, 2021 , Pitts, 2021 ). Part of the disproportionate burden on women is attributable to the impact of the pandemic on the service sector, which typically employs more women than men (Alon et al, 2020b ).…”
Section: Related Literaturementioning
confidence: 99%
“…Owing to the employment structure of different sectors, the COVID-19 pandemic may have an unequal impact on the employment and earnings of different labourers. Several studies have found that labourers who are older, have a low level of education, non-regular employees, and female would suffer greater losses [10][11][12][13][14][15][16]. Thus, the first research hypothesis of the study is that the COVID-19 pandemic would have an unequal impact on the labour market.…”
Section: Introductionmentioning
confidence: 97%
“…The effect of unemployment on domestic violence is theoretically ambiguous and has many potential channels. Unemployment can create family stress, which leads to more violence; additionally, household bargaining theory predicts that a sharp increase in female unemployment and a mild increase in male unemployment, as was the case in 2020 (Albanesi & Kim, 2021 ), would increase domestic violence due to a relative shift in economic bargaining power towards men. However, theories of male backlash and instrumental violence predict that female unemployment would lead to less domestic violence.…”
Section: Discussionmentioning
confidence: 99%